Production and reproduction performances of exotic breeds of rabbit under tropical climatic conditions of Tamil Nadu - SIVAKMAR, K; KUMAR, V RAMESH SARAVANA; THIRUVENKADAN, A K; SARAVANAN, R; JEYAKUMAR, M (The Indian Journal of Animal Sciences, 2012)
Data on 755 kindlings observed in White Giant (n,374) and Soviet Chinchilla (n,381) breeds of rabbits between the year 2005 and 2009, were analyzed to assess the influence of genetic and non-genetic factors on different traits at tropical climatic conditions of Tamil Nadu. The overall least-squares means for litter size at birth and weaning, litter weight at birth and weaning and pre-weaning growth rate were 5.1, 3.9; 260.5 g, 2537.6 g; 51.6 g, 668.4 g and 14.5 g, respectively. Breed had highly significant effect only on litter weight at weaning, individual kit weight at weaning and pre-weaning growth rate. In general, year and season of birth had significant to highly significant effect on all the traits studied. The heritability estimates obtained for litter size at birth and weaning and litter weight at birth and weaning were 0.469, 0.493; 0.475 and 0.309, respectively. Monsoon season (June to Nov) were the most favourable season, whereas summer (March to May) proved to be the most unfavourable season for different production traits. Because of higher heritability estimates, mass selection is recommended for genetic improvement of the production traits in White Giant and Soviet Chinchilla breeds of rabbit.